Development and Testing of a M-Learning System for the Professional Development of Academics Through Design-Based Action Research - Ozdamar Keskin, Nilgun; Kuzu, Abdullah (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2015)
In the present study, a mobile learning system for the professional development of academics was developed by design based action research, and the perceptions and experiences of the academics using this system were examined. In the first phase of this design-based action research, the research question was defined. In the second phase, a m-learning system called “Mobile Academic Research Support” (MARS) was designed as a solution to the problem, and the IOS mobile application for this design was developed. In the third phase of the study, the MARS application was regularly tested and evaluated by the academics over eight weeks. At the end of the research process, the results were reflected upon. It was found that the primary and important professional development needs of the academics were at the scientific research level. It was also observed that the m-learning system developed for the professional development of the academics regarding scientific research was appropriate to the overall purpose, accessible, adaptable and appealing; that it served both as a m-learning and as an academic support system; that its content was satisfactory; and that the tools used in the system were useful. In addition, it was observed that the academics were able to use mobile technologies for learning. Also, it was stated that such a system could provide positive contributions to the professional development of academics.